2016
DOI: 10.1016/j.molcel.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

U2AF35(S34F) Promotes Transformation by Directing Aberrant ATG7 Pre-mRNA 3′ End Formation

Abstract: SUMMARY Recurrent mutations in the splicing factor U2AF35 are found in several cancers and myelodysplastic syndrome (MDS). How oncogenic U2AF35 mutants promote transformation remains to be determined. Here we derive cell lines transformed by the oncogenic U2AF35(S34F) mutant, and identify aberrantly processed pre-mRNAs by deep sequencing. We find that in U2AF35(S34F)-transformed cells the autophagy-related factor 7 (Atg7) pre-mRNA is abnormally processed, which unexpectedly is not due to altered splicing but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(143 citation statements)
references
References 55 publications
7
135
1
Order By: Relevance
“…In contrast, several recent studies have identified that ablation of the mutant RNA splicing factor allele appears to have no effect on cancer maintenance. 11,25,44 This was demonstrated in 2 studies where deletion of the mutant U2AF1 S34F or SF3B1 …”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, several recent studies have identified that ablation of the mutant RNA splicing factor allele appears to have no effect on cancer maintenance. 11,25,44 This was demonstrated in 2 studies where deletion of the mutant U2AF1 S34F or SF3B1 …”
mentioning
confidence: 91%
“…8, [23][24][25] Although there have been major advances in understanding the role of RNA splicing factor mutations in MDS pathogenesis and therapy (as reviewed recently [26][27][28] ), major questions about their biological consequences within cells, requirement in disease initiation vs maintenance, and cell autonomous vs nonautonomous roles remain. In addition, numerous questions about the structural and biochemical effects of the mutations on protein-protein and protein-RNA interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 In addition, a recent study demonstrated that ectopic expression of S34F U2AF1 in Ba/F3 cells resulted in increased use of distal mRNA cleavage and polyadenylation sites. 66 One of the affected transcripts was Atg7, which led to reduced protein levels and a functional autophagy defect.Deep sequencing analysis of U2AF1 mutant patient samples, transgenic mice, and isogenic cell lines have demonstrated the presence of global changes that affect 5% to 10% of the transcriptome.52,57 Some of these recurrent alternatively spliced genes are implicated in essential cellular processes, such us RNA processing and splicing, protein translation, DNA methylation, and DNA damage response and apoptosis, and can also occur in genes that are recurrently mutated in MDS. 52,57,58,63,64,67 However, the functional contribution to the disease phenotype of alternatively spliced genes remains an active area of research.…”
mentioning
confidence: 99%
“…Park et al, show that the U2AF35 mutant promoted the usage of a distal poly(A) site in Atg7 mRNA, thus generating a longer, inefficiently translated transcript. Decreased ATG7 led to mitochondrial dysfunction including genomic instability, which induces cells to acquire secondary mutations disposing them to transformation [53] .…”
Section: Hnrnp P2mentioning
confidence: 99%